Polymer Biowaste Hybrid for Enhanced Piezoelectric Energy Harvesting - Gaur A.; Tiwari S.; Kumar C.; Maiti P. (My University, 2025)
A green composite, derived from the biowaste pomegranate peel, is used for piezoelectric energy harvesting. A hybrid of poly(vinylidene fluoride) and pomegranate peel powder is prepared through a solution route. A structural change of the polymer matrix from the nonpiezo to piezoelectric phase in the presence of a filler has been revealed through X-ray diffraction, spectroscopic, and calorimetric studies. Piezoelectric biowaste induces piezoelectricity in the polymer matrix, which is further confirmed through a range of morphological studies (optical, electronic, and atomic force microscopy). A model has been developed to focus on the synergism between two piezoelectric phases (matrix and filler), which is appropriate for energy harvesting. A device has been fabricated using the hybrid, which exhibits a high open circuit voltage and a power density of 65 V and 84 μW/cm2. The developed device is also able to generate power under human movements such as walking, twisting, and bending, and the power is sufficient to light up LEDs and can be stored using a capacitor. Copyright © 2020 American Chemical Society.